2007
DOI: 10.7132/jrcsa.kj00004557612
|View full text |Cite
|
Sign up to set email alerts
|

GA-designed Fuzzy Rule-based System for Parameter Estimation of Distributed Rainfall-runoff Model Considering Various Cell Characteristics

Abstract: A fuzzy rule-based system, designed with genetic algorithm (GA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The conceptual model parameters were identified on a trial and error basis, considering their physical meanings and referring to the published works (Alam et al 2006(Alam et al , 2007Nakagiri et al 1998), so that the reported results of the annual evapotranspiration (Lake Biwa Research Institute 1988), and the annual amounts of irrigation water and groundwater recharge from paddy fields (Mitsuno and Nagahori 1987) could also be obtained from the model. Furthermore, the time-varying groundwater levels observed at the boring points B5 and B6 from September 1st, 2006 to March 31st, 2006 were used for calibration of the model.…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The conceptual model parameters were identified on a trial and error basis, considering their physical meanings and referring to the published works (Alam et al 2006(Alam et al , 2007Nakagiri et al 1998), so that the reported results of the annual evapotranspiration (Lake Biwa Research Institute 1988), and the annual amounts of irrigation water and groundwater recharge from paddy fields (Mitsuno and Nagahori 1987) could also be obtained from the model. Furthermore, the time-varying groundwater levels observed at the boring points B5 and B6 from September 1st, 2006 to March 31st, 2006 were used for calibration of the model.…”
Section: Calibrationmentioning
confidence: 99%
“…For this, our earlier distributed watershed model (Alam et al 2006(Alam et al , 2007 is revised and sophisticated in which the soil moisture model is incorporated to evaluate runoff processes and evapotranspiration depending dynamically on water contents retained in the surface soil. Part of the subsurface tank model built in this watershed model is replaced with a mathematical unconfined shallow groundwater flow model, and in addition a network of on-farm drainage canals is considered so that the model could successfully be applied to a watershed including farmlands in a low-lying area.…”
Section: Introductionmentioning
confidence: 99%
“…Though it seems short, Sorooshian et aL (1983) suggested that rather than length, the quality of infbrmation contained in the data is important. For calibra-tion of the model parameters, the GA-designed fuzzy system (Alam et al, 2007) is employed, which can allow for both qualitative and quantitative information of attributes in a watershed, but takes more time. Therefore, short length of data set would be favorable to avoid huge time requirement.…”
Section: Studyareamentioning
confidence: 99%